2018
DOI: 10.1002/chem.201802448
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1‐Aminoindenes through Aza‐Prins‐Type Cyclization

Abstract: An acid-catalyzed aza-Prins-type endo cyclization of 2-alkenylbenzaldehydes with BocNH or aniline derivatives through in situ generation of iminium intermediates has been developed, and various 1-aminoindene derivatives were readily obtained. The first catalytic asymmetric variant of the present reaction has also been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…1C) reported the first asymmetric Brønsted acid-catalyzed aza-Prins type endo cyclization of 2-alkenylbenzaldehydes with BocNH2 or anilines through in situ generation of iminium intermediates to generate chiral 1-aminoindenes, however, only five examples have been demonstrated and moderate to good ee values were obtained. 11 Recently, our research group reported a BINOLderived chiral N-triflyl phosphoramide (NTPA) catalyzed enantioselective intramolecular iminium ion cyclization reaction Click here to insert a dedication.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…1C) reported the first asymmetric Brønsted acid-catalyzed aza-Prins type endo cyclization of 2-alkenylbenzaldehydes with BocNH2 or anilines through in situ generation of iminium intermediates to generate chiral 1-aminoindenes, however, only five examples have been demonstrated and moderate to good ee values were obtained. 11 Recently, our research group reported a BINOLderived chiral N-triflyl phosphoramide (NTPA) catalyzed enantioselective intramolecular iminium ion cyclization reaction Click here to insert a dedication.…”
Section: Figurementioning
confidence: 99%
“…the generation of iminium intermediates in situ to give chiral 1-aminoindenes (Figure 1C); however, only five examples were examined, and moderate to good ee values were obtained. 11 We recently reported an enantioselective intramolecular iminium-ion cyclization reaction of 2-alkenylbenzaldimines catalyzed by a BINOL-derived chiral N-triflylphosphoramide (NTPA) for the synthesis of chiral 1-aminoindenes and tetracyclic 1-aminoindanes. 12 We commenced our reaction-condition screening by investigating a variety of chiral Brønsted acid catalysts PA1-8 for cyclization of the model substrate 1a in toluene at 60 °C (Scheme 1).…”
Section: Synpacts Synlettmentioning
confidence: 99%
See 2 more Smart Citations
“…The control of the stereochemistry in the aza-Prins reaction has been recently studied by several groups. Maruoka and Kano reported the asymmetric aza-Prins-type cyclization in the presence of chiral phosphoric acid, 5 and Dobbs reported the stereoselective aza-Prins reaction by introducing a chiral auxiliary to the homoallylamine. 2c , 6 The enantiopure nitrogen heterocycles synthesized by these studies are expected to be important intermediates for the synthesis of biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%